Exploring the Anti-Pulmonary Fibrosis Mechanism of Jingyin Granule by Network Pharmacology Strategy - Zhu, De-wei; Yu, Qun; Jiang, Mei-fang; Wang, Dan-dan; Shen, Yun-hui (Frontiers in Pharmacology, 2022)
pulmonary fibrosis (PF) is a clinically common disease caused by many factors, which will lead to lung function decline and even respiratory failure. Jingyin granule has been confirmed to have anti-inflammatory and antiviral effects by former studies, and has been recommended for combating H1N1 influenza A virus (H1N1) infection and Coronavirus disease 2019 (COVID-19) in China. At present, studies have shown that patients with severe COVID-19 infection developed lung fibrotic lesions. Although Jingyin granule can improve symptoms in COVID-19 patients, no study has yet reported whether it can attenuate the process of PF. Here, we explored the underlying mechanism of Jingyin granule against PF by network pharmacology combined with in vitro experimental validation. In the present study, the active ingredients as well as the corresponding action targets of Jingyin granule were firstly collected by TCMSP and literature data, and the disease target genes of PF were retrieved by disease database. Then the common targets were subjected to Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses, then PPI network and ingredient-target network was constructed. Next, UPLC-MS was used to isolate and identify selected representative components in Jingyin granule. finally, LPS was used to induce A549 cell fibrosis model to verify the anti-PF effect of Jingyin granule in vitro. Our results indicated that STAT3, JUN, RELA, MAPK3, TNF, MAPK1, IL-6, and AKT1 were core targets of action and binded with good affinity to selected components, and Jingyin granule may alleviate PF progression by Janus kinase 2/signal transducers and activators of transcription (JAK2/STAT3), the mammalian nuclear factor-κB (NF-κB), the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt), tumor necrosis factor (TNF), the extracellular signal-regulated kinases 1 and 2 (ERK1/2) signaling pathway. Overall, these results provide future therapeutic strategies into the mechanism study of Jingyin granule on PF.